COMPARISON OF LEVELS OF SELF-ESTEEM BY SEX AND LEVEL OF PHYSICAL ACTIVITY IN TWO GROUPS OF SENIOR ADULTS - Rodríguez-Méndez, Diego; El Hob Montero, Wady; Solano Mora, Luis (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2016)
The study explores children’s perceptions regarding physical activity barriers and facilitators during recess in order to provide the necessary input for governmental authorities and educational researchers to develop policies and interventions that promote physical activity for this age group within the educational environment. Methods: A qualitative design was employed that used focus groups and in-depth interviews for data collection. Data was collected from six focus groups, which included a total of 90 third-graders (50 boys and 40 girls) and their three teachers. Results: The most frequent barriers identified by children were: a lack of social support, bulling, a lack of space, and organizational barriers. A lack of space and time was a barrier for all children, resulting in conflict and exclusion from physical activities for girls and some of the boys. Conclusion: Participants perceive the school environment as not favorable for physical activity; however, following their nature and need to move, a large majority finds ways to fill that need to play and have fun. Based on the results of this study, physical activity should be promoted during recess, taking into consideration barriers in the natural, social, physical and organizational environments.